Human demography changes in Morocco and environmental imprint during the Holocene. (May 2019) - Cheddadi, Rachid; Palmisano, Alessio; López-Sáez, José Antonio; Nourelbait, Madja; Zielhofer, Christoph; Tabel, Jalal; Rhoujjati, Ali; Khater, Carla; Woodbridge, Jessie; Lucarini, Giulio; Broodbank, Cyprian; Fletcher, William J; et al.
The aim of this work is to reconstruct the periods of growth and decline of human populations in Morocco and their potential impacts on the landscape over the past 10, 000 years. In order to estimate the trends in the human population size between 10, 000 and 3000 years ago, we used a summed probability distribution (SPD) of radiocarbon dates from a wide range of archaeological sites throughout Morocco. Landscape changes were identified and quantified from a dataset of fossil pollen records. Different anthropogenic pollen markers, as well as natural vegetation groups and taxonomic richness were used to analyse the relationship between long-term trends in human population expansion or regression and type of impact on the landscape. The sub-regions of Morocco have different topographies and climates, which have either favoured or prevented the establishment and/or spread of human populations. In order to identify the areas most significantly impacted by humans and the timing of such impacts, we have reconstructed and compared the same past anthropogenic and landscape proxies along with the population trends within the lowlands and mountainous areas. The lowlands were more strongly impacted earlier in the Holocene than the mountainous areas. Anthropogenic markers indicate that farming expanded in the lowlands during the first major expansion of human populations between ca. 7200 and 6700 cal. yr BP at the start of the Neolithic period. In the Atlas and Rif Mountains, anthropogenic impact is not clearly detectable in any of these areas before 4000 cal. BP.